2023
DOI: 10.1186/s42836-023-00165-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between gaits after a medial pivot and posterior stabilized primary total knee arthroplasty: a systematic review of the literature

Abstract: Background Total knee arthroplasty (TKA) is one of the most performed orthopedic procedures worldwide. While excellent efficacy has been reported, about 20% of patients are not satisfied with the result. A potential cause is the problematic reproduction of knee kinematics. This systematic review examines gait analysis studies in primary medial pivot (MP) and posterior stabilized (PS) TKAs to investigate the differences between the two prosthesis designs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The American Knee Society (AKS) score and Western Ontario and MacMaster (WOMAC) were used for clinical evaluation [ 20 , 21 ]. Regular follow-up evaluations were performed at the outpatient department at 6 weeks, 3 months, 6 months, and 1 year after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The American Knee Society (AKS) score and Western Ontario and MacMaster (WOMAC) were used for clinical evaluation [ 20 , 21 ]. Regular follow-up evaluations were performed at the outpatient department at 6 weeks, 3 months, 6 months, and 1 year after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Following knee arthroplasty, knee mechanics partially restore [ 14 , 15 ], although functional deficits often remain when compared to healthy controls [ 16 ]. Post TKA, individuals typically show reduced knee excursion (i.e., lower functional range of motion) and reduced external knee flexion moments [ 17 , 18 ], that may be attributed to reduced knee extensor strength [ 19 ]. Evaluating knee biomechanics post-operatively during TKA recovery may better describe post-operative knee function, objectively inform rehabilitation decisions, and lend itself to improved surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the use of CPM has advantages over physical therapy, including reduced swelling, faster return of joint mobility, and reduced analgesia [ 14 ]. However, there is still a great deal of controversy about whether it is beneficial for patients' postoperative recovery in the past two decades of research [ 4 , 15 18 ]. Many researchers support these benefits; on the contrary, many studies show that the advantages of CPM compared to physical therapy are not as clear [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%